An Epidemic of Complexity: Polysubstance Use Fatal Overdose Typologies Across Cook County, Illinois, Neighborhoods, 2017‒2022. - Cadet, Kechna; Martins, Silvia S.; Nesoff, Elizabeth D. (American Journal of Public Health, 2026)
Objectives. To examine geospatial polysubstance use overdose typologies and socio-structural determinants among overdose decedents in Cook County, Illinois, from 2017 to 2022. Methods. Decedents' addresses were geocoded and aggregated to census tract level (n = 1331). We conducted latent profile analysis to identify census tract profiles based on overdose fatality rates per 1000 census tract population across 9 drug types (alcohol, fentanyl, prescription opioids, heroin, cocaine, benzodiazepines, xylazine, methamphetamine/amphetamine, and other drugs). We used Bayesian spatial multinomial logistic regression to determine what census tract socio-structural determinants could predict polysubstance profile membership. Results. Three clusters of polysubstance use—low, moderate, and high—emerged with fentanyl, cocaine, and heroin dominating all clusters. In the adjusted model, census tracts with lower median household income were associated with increased odds of belonging to the moderate polysubstance use profile (odds ratio [OR] = 0.90; 95% Bayesian credible interval [CrI] = 0.85, 0.96) compared with the referent group. Also, census tracts with high Black isolation (quartile 4: OR = 2.93; 95% CrI = 1.44, 6.02) and higher population density (OR = 1.24; 95% CrI = 1.13, 1.37) were more likely to belong in the high polysubstance use profiles. Conclusions. Findings support the need for targeted resources tailored for particular neighborhoods. (Am J Public Health. 2026;116(8):1210–1219. https://doi.org/10.2105/AJPH.2026.308446)